THE EFFECT OF FINANCIAL BENEFITS PERCEPTION ON CUSTOMER LOYALTY WITH BSI BANK CUSTOMER SATISFACTION AS A MEDIATION VARIABLE - Rico Syahputra; Rahmat Maulidan; Imam Gunanjar; Muhammad Ridwan Verinanda (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the direct influence of perceived financial benefits on BSI Bank customer loyalty, as well as the indirect influence through customer satisfaction as a mediating variable. Financial benefits are the main attraction of Islamic banking products, but the sustainability of customer relationships is highly dependent on the loyalty built. This study uses a quantitative approach with a survey method on BSI Bank customers. Data were collected using questionnaires and analyzed using path analysis techniques through SmartPLS software to test the relationship between variables and the role of mediation. The results of the study are expected to show that: (1) Perceived financial benefits have a positive and significant effect on BSI Bank customer satisfaction; (2) Perceived financial benefits have a positive and significant effect on BSI Bank customer loyalty; (3) Customer satisfaction has a positive and significant effect on BSI Bank customer loyalty; and (4) Customer satisfaction significantly mediates the influence of perceived financial benefits on customer loyalty. The findings of this study are expected to provide theoretical contributions to the development of banking services marketing literature, especially Islamic banking, as well as practical implications for BSI Bank management in designing product strategies, pricing, and customer relationship programs that not only offer financial benefits but also increase satisfaction to build long-term loyalty.